Ewolucja sfery publicznej i mechanizmów zarządzania publicznego w kontekście wytwarzania "wiedzy uwspólnionej" = The evolution of the public sphere and public managament mechanisms in the context of the creation of "shared knowledge" - Mazur, Stanisław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to analyse changes ensuing in the public sphere and in public management rules, as well as to conceptualize their interdependence in the context of the creation of shared knowledge. The research question is to what extent the public sphere (characterized by a low capacity to create shared knowledge) leads to the dysfunctionality of the public management system. An equally important question is how the incapacity to create shared knowledge weakens the ability to minimize tensions over values-based disputes and reduces group problem-solving mechanisms.
Keywords: sfera publiczna; spójność normatywno-funkcjonalna; wiedza uwspólniona; zarządzanie publiczne; public sphere; normative and functional unity; shared knowledge; public management